Peripheral Demyelinating Diseases: From Biology to Translational Medicine - Kamil, Khidhir; Yazid, Muhammad Dain; Idrus, Ruszymah Bt Hj; Das, Srijit; Kumar, Jaya (Frontiers in Neurology, 2019)
Demyelinating diseases represent a spectrum of disorders that impose significant burden on global economy and society. Generally, the prognosis of these diseases is poor and there is no available cure. In recent decades, research has shed some light on the biology and physiology of Schwann cells and its neuroprotective effects in the peripheral nervous system (PNS). Insults to the PNS by various infectious agents, genetic predisposition and immune-related mechanisms jeopardize Schwann cell functions and cause demyelination. To date, there are no effective and reliable biomarkers for PNS-related diseases. Here, we aim to review the following: pathogenesis of various types of peripheral demyelinating diseases such as Guillain-Barre syndrome, Chronic Inflammatory Demyelinating Polyradiculoneuropathy, Anti-Myelin Associated Glycoprotein Neuropathy, POEMS syndrome, and Charcot-Marie-Tooth disease; emerging novel biomarkers for peripheral demyelinating diseases, and Schwann cell associated markers for demyelination.